Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content: 1. The Impact of Friendship in Workplace on Job Commitment: A Field Study in Private Sector Automotive Companies in Saudi Arabia Mr. Ahmed Farouk A. Mohammed 2. Financial Management: Foundations and Contemporary Challenges Ms. Ruwaida Saeed Alshehri 3. The role of self-financing in achieving financial independence and academic quality in government higher education institutions in the Sultanate of Oman: An analytical study of challenges and opportunities Ms. Noora Ahmed Al-Busaidi, Dr. Hafida Nia 4. The Extent of the Affection of Some Factors on the Responsibility of External Auditor for Detection and Reporting Fraud Operations: An Empirical Study in the Kingdom of Saudi Arabia Ms. Bdour Saeed Alrefai 5. Challenges of Using Artificial Intelligence in Human Capital Management at the Communications, Space, and Technology Commission in the Kingdom of Saudi Arabia Dr. Ahlam Melfi Alotaibi 6. Marketing is a Positive Force in Contemporary Society: Case of Holland & Barrette Social Campaign Ms. Ohoud Mohammed Algarni 7. Holland & Barrett Health and Wellbeing Retailers Social Marketing Campaign: Case of Saudi Arabia Implementation Ms. Ohoud Mohammed Algarni